An exploratory pilot study of mathematics performance patterns: visual art students vs. non-art students - Cao, Yu (Frontiers in Psychology, 2025)
This is an exploratory pilot study designed to identify preliminary patterns in mathematics performance. A longitudinal comparative design was adopted, analyzing mathematics scores of 37 art students and 40 non-art students from a Chinese university across four consecutive semesters. Descriptive statistics characterized overall performance, independent samples t-tests (with Bonferroni correction) assessed between-group differences per semester, Pearson correlation coefficients examined intra-individual score consistency, ANCOVA (with gender as a covariate) and subgroup analyses explored gender effects, and trend analysis tracked longitudinal changes. Post-hoc power analysis confirmed sufficient power (0.809–0.899) to detect moderate effects. Non-art students demonstrated consistently higher numerical mathematics scores than art students across all semesters (75.6–78.9 vs. 70.2–73.5). After Bonferroni correction (α = 0.0125), t-tests confirmed statistically significant differences only in Semester 3 (t = −2.43, p = 0.017). Mann–Whitney U-tests were applied to validate t-test results for Semester 2 (mixed normality) and Semester 3 (non-normal data), confirming the Semester 3 significance (U = 393.5, p = 0.000) and consistency of non-significant findings in Semester 2. Gender subgroup analyses revealed the gap was driven exclusively by female students (non-art: M = 81.12 vs. art: M = 74.56, p = 0.006), while males showed no differences (p = 0.963). Correlation analysis revealed stronger score stability among non-art students (r = 0.62–0.78) compared to art students (r = 0.51–0.65). Both groups showed a gradual upward trend (art: +3.3 points; non-art: +3.3 points), but the numerical performance gap remained stable (5.2–5.4 points). Preliminary patterns of persistent mathematics performance differences highlight the need for targeted support to balance artistic and academic development for art majors.